Women with wings imaging the women in contemporary West Visayan poetry - Lopez, Ferdinand M. (2003)
The more than three hundred years of Spanish colonization and the more than fifty years of American imperialism in the archipelago have resulted in the brain-washing and the soul-washing of its people. Colonization, through its powerful appendages- religion and education symbolized by the cross and the classrooms, respectively-have succeeded in disenfranchising women, gays, and others who were considered the epistemological "other" of the male conquistadores. Patriarchal institutions and structures reproduce images and values which are inimical to women's well-being. As a result, women are misrepresented and muted in political and imaginative discourses where gender stereotyping reinstates and reinforces the male's stake to power and control. This study endeavors to identify the images of women in thirty contemporary West Visayan poetry. Specifically, this paper purports to answer the following questions: (a) how does society construct women and condition her representation in the texts?; and (b) how does gender affect the portrayal of women? By displacing androgenic hegemony through feminist interventions such as a rekindling of the babaylanic tradition and a repeated cultural exorcism, the individual can begin to interrogate and read against the grain the problematics of gender construction and politics.